Sol-gel prepared Cu2ZnSnS4 (CZTS) semiconductor thin films: Role of solvent removal processing temperature - Ahmoum H.; Chelvanathan P.; Su'ait M.S.; Boughrara M.; Li G.; Gebauer R.; Sopian K.; Kerouad M.; Amin N.; Wang Q. (Elsevier Ltd, 2023)
Carrier concentration; Copper compounds; Crystallinity; Crystallite size; Energy gap; Morphology; Semiconducting tin compounds; Sol-gel process; Sol-gels; Solar cells; Surface morphology; Zinc compounds; Condition; CZTS; Preheating temperature; Processing temperature; Role of solvents; Semiconductors thin films; Sol'gel; Solvent removal; Sulphuration; Thin-films; Thin films